URGENSI ETIKA KOMUNIKASI ISLAM BAGI PENDIDIK DALAM DUNIA PENDIDIKAN - Fajri Chairawati Fajri Chairawati; Asyraf Andari Harisma; Wildia Ulfita Ladayani (Lembaga Sepercenter, 2025)
The world of education plays a very important role in shaping the character and personality of students, where the importance of involving the role of Islamic communication ethics in the world of education carried out by educators is often overlooked and not applied. However, this is necessary to create harmonious interactions between educators and students. Therefore, Islamic communication ethics are very important for educators in carrying out their duties and responsibilities. This study will discuss the urgency of Islamic communication ethics for educators in education, using a research method that involves reviewing books, journals, and related references on Islamic communication ethics in education. The application of Islamic communication ethics in education will enhance the quality of Islamic educational interactions between educators and students by adhering to the principles and ethics of Islamic communication. This will ultimately create a harmonious, inclusive, and Islamic learning environment.